Modified basicity of MgFe mixed metal oxides catalysts for glycerol conversion to form glycerol carbonate via the transesterification route - Sakhile T. Dube; Lindelani Q. Qwabe; Holger B. Friedrich (Applied Catalysis O: Open)
Mixed metal oxides (MMOs) of magnesium and iron, with different Mg:Fe ratios, were synthesized via co-precipitation and used for the transesterification of glycerol (GLY) with dimethyl carbonate (DMC). The hydrotalcite-like precursors with corresponding mixed metal oxides were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), N2 adsorption-desorption, temperature-programmed NH3 desorption (TPD) and CO2 temperature-programmed desorption (TPD). XRD analysis of the precursor confirmed the presence of hydrotalcite-like species, whereas their calcined form showed the formation of MgO, Fe2O3 and MgFe2O4 spinel. The binding energies at 1305 and 710 eV in the XPS showed the presence of Mg2+ and Fe3+. The CO2-TPD results show that the basicity of the material increases with increasing MgO content, while the NH3-TPD shows that the acidity decreases with decreasing Fe3+ content. An increase in the MgO phase favoured the formation of glycerol carbonate (GC) with a selectivity of 95 %. Recycle experiments showed that the catalysts were stable and gave conversions of 93 % and selectivity of 95 % very close to those of the fresh catalysts.